Assessing Contact, Coverage, and Quality of continuum of care in Uttar Pradesh, India. (30th September 2020) - Gupta, S; S, K; Yonzon, K; Kumar, P; Choudhry, V
Abstract: Background: Given the high neonatal mortality in LMIC, strategies suggest a continuum of care (COC) as an effective framework to ensure timely and appropriate service provision throughout the MNCH continuum. However, the measurement approaches traditionally focus on assessing continuum of care from the lenses of time-based coverage and missing out on the quality of coverage and service delivery. This paper aims to assess the continuum of care based on these three parameters and the factors affecting its achievement. Methods: Multistage sampling design identified live births and stillbirths in the last calendar year (March 2018-February 2019) across the 50 districts of Uttar Pradesh(n = 16646).COC was assessed on three measurements 1) Contact: Any contact with the health system across the continuum, 2)Coverage: Adequate contacts of the health system through outreach services and clinical care, and 3)Quality: receiving adequate services along with these contacts. Further, a multilevel regression model was used to estimate the factors associated with the continuum of care. Results: 64% (60.04-67.65) of the women and child received health system contact across the continuum while only 2.1% (1.57-2.78) and 2.8% (2.33-3.44) women and children achieved coverage and quality based COC, respectively. Achievement of COC coverage and COC quality is highly affected by the service delivery platform, with women at outreach platform being more likely to achieve adequate coverage while women at facilities are more likely to achieve quality services across ANC, delivery, and PNC. Conclusions: Achievement of both coverage and quality based COC remains low in Uttar Pradesh, India. Even those who achieve contact(s) failed to receive quality services along with these contacts with health systems. Efforts should be focused on building quality service at the outreach and non-outreach platforms across the continuum of care for reducing the risk of neonatal mortality. Key messages: Owing to the lack of an integrated approach for service delivery across outreach, clinical care and community care, continuum of care remains broken for most of the mothers and children. For targeting coverage and quality of COC, focus should be on improving the quality of service provision across the outreach platforms which are already in reach of the women.